(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The analysis of Gabriela Mistral´s poem Little Red Riding Hood is appealing since its composition confirms the insuperable quality of the author´s poetic work. However, the fact that the story finds its origins in the European folklore and that it became known worldwide due to its modern versions (Perrault and the Brothers Grimm), turn the poem into a curiosity. The purpose of the analysis is to describe of the erotic dimension of the linguistic discursive resources used by Mistral to recreate the story and restore the meaning of the original text, probably recovering its reading as crime, shattered innocence, and the pain that it conveyed.